There is nothing old under the sun = Llevaba un sol adentro - Pasqual Esparza, Daniela (Taideyliopiston Teatterikorkeakoulu, 2021)
Abstract in English: There is nothing old under the sun took place at Helsinki’s Winter Garden on March 14th and 15th 2020. Inspired by Tarot as a speculative practice, the performance consisted of thirty-minute long one-on-one card-reading sessions. We created our deck based on twelve plants from the garden, and we researched each of these plants. With the information we were able to gather, we designed two card spreads for participants to choose from: the first addressed a question of their choice while the second focused on their presence in the Winter Garden. None of the spreads dealt with fortune-telling; instead, they attempted to create a space to play, think, and making connections. At the end of each reading, we invited the audience to keep exploring the garden in the company of a zine. The written section of my thesis is, in essence, a documentation of the creative process. Three questions have kept me company along my journey, and they give voice to each chapter of the thesis. They are, in order: What does it mean to see? What does it mean to be autonomous? How to work for space? The first chapter sheds some light on how I reached the Winter garden, the deck, and predictive techniques. The second focuses on the context of the piece. I reflect on my studies, the collaboration with my colleagues, and the relationship with the audience. In the third chapter, I briefly contextualize my approach to space in this work and share the material we used to engage with the Winter Garden and the card-deck. Finally, I’ve chosen to write in English and Spanish because I would like my family to read me in our shared language. Bilingualism has also been a feature of this piece since its beginnings, and it’d be incongruous to sacrifice it now. Resumen en castellano: Llevaba un sol adentro tuvo lugar en el Jardín de invierno de Helsinki el 14 y 15 de marzo del 2020. Inspirándonos en el tarot como práctica especulativa, planteamos lecturas de cartas de treinta minutos como un ejercicio de observación e imaginación. Las cartas de nuestra baraja evocan doce plantas del jardín. Investigamos cada una de ellas y luego diseñamos dos tiradas. La primera exploraba una pregunta de interés para la persona que hacía la consulta, mientras que la segunda prestaba atención a su presencia en el Jardín de invierno aquel día. Las tiradas poco tenían que ver con adivinar o predecir el futuro: más bien, buscaban habilitar un espacio para jugar, hilar y pensar en compañía. Después de las lecturas, cada participante podía seguir explorando el jardín con un fanzine. Esta tesina es, ante nada, una documentación del proceso creativo. Hay tres preguntas que me han acompañado a lo largo del camino y que hoy me permiten estructurar los capítulos de este escrito. En orden: ¿Qué significa mirar? ¿Qué significa ser autónoma? ¿Cómo trabajar al servicio de un lugar? El primer capítulo esclarece cómo llegué al Jardín de invierno, también la lógica de la baraja o nuestra relación con las técnicas predictivas. El segundo se centra en el contexto de la pieza. Reflexiono sobre mis estudios, la colaboración con mis colegas, y la relación con el público. En el tercero, contextualizo brevemente mi relación con lo espacial en el marco de este trabajo, y comparto el material que utilizamos para acercarnos a la baraja y al Jardín de invierno. Por último, he decido escribir en inglés y en castellano porque me gustaría que mi familia pueda leerme en nuestro idioma. Además, el bilingüismo ha sido, desde un inicio, una característica de esta pieza, y sería incongruente sacrificarlo a estas alturas.
Keywords: card reading; to see; viewpoint; Helsinki’s Winter Garden; Performance art; Plant life; Vision; Autonomy; Space; Helsingin kaupungin talvipuutarha; talvipuutarhat; kasvitieteelliset puutarhat; kasvillisuus; performanssi; esitystaide; kokeminen; autonomia; tila; LAPS